Dialogue as a Means of Collective Communication
XIV, 440 p.
Keywords: Dialogue as a Means of Collective Communication offers a cross-disciplinary approach to examining dialogue as a communicative medium. Presented in five parts, the book takes the reader on a journey of exploring the power and potential of dialogue as a means for communication. In particular, this volume comes at a time when the global society's attention has been directed to creating more productive conversations in the name of world peace and harmony. It provides a unique new work on dialogue that brings the reader into a "dialogue with dialogue", offering an opportunity to understand the communicative potential of dialogue. In the book, readers are introduced to five sections: Section I examines the historical and cultural perspectives of conversation. This examination helps to create a foundation for a deeper study of the emergent and salient aspects of conversation as it relates to cultural creativity and human systems design. Sections II offers the reader an examination of dialogue through different philosophical and theoretical perspectives as well as methodological ideas related to conversation. Section III explores different modalities of conversation and the application of design conversation within and across various types of design settings and human experiences. Section IV examines the field of practice as related to use of different forms of conversation. Here various authors will share their different approaches to conversation and their reflections and insights in using conversation in a variety of settings. Concluding the book, Section V reflectively examines the authors' contributions to the book and provides the reader with a focus on the future.